2018
DOI: 10.1186/s12886-018-0806-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the MyoRing implantation depth by mechanical dissection using PocketMaker microkeratome versus Melles hook via AS-OCT

Abstract: BackgroundThis paper seeks to evaluate the depth and outcomes of MyoRing implantation using two mechanical dissection procedures including: PocketMaker microkeratome in opposition to the Melles hook method.MethodsThis retrospective study was carried out on 39 eyes of 38 keratoconus patients (28 male and 10 female) with the mean age of years and had undergone MyoRing implantation by the two mentioned methods. The MyoRing was inserted into the corneal pocket which was made manually in 18 eyes (Melles hook group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…3 ). Femtosecond laser-assisted surgery was used to ensure accuracy and reproducibility, but intrastromal pocket creation can be achieved manually without a laser 45 , 46 .…”
Section: Resultsmentioning
confidence: 99%
“…3 ). Femtosecond laser-assisted surgery was used to ensure accuracy and reproducibility, but intrastromal pocket creation can be achieved manually without a laser 45 , 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Mean keratometry reduction was 6.1 ± 0.4 and 6.2 ± 3.55 in the PocketMaker and Melles hook, respectively. UCVA change ( P = 0.76), CDVA change ( P = 0.77), and K-means change ( P = 0.69) showed that there was no statistically significant difference between both groups for any parameter [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of a full corneal intrastromal ring as an additive refractive technique for the correction of myopia was first proposed by Reynolds in 1978 [ 6 ]. Extensively enhanced by Daxer [ 7 ], implantation of a full corneal intrastromal implantation system (CISIS) has been considered for KC management [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%